Correspondence of larval and postlarval instars in two species of the subgenus Zaracarus (Acari: Erythraeidae: Erythraeus) established with laboratory rearing - Karakurt İbrahi̇m; Wohltmann, Andreas; Pamuk, Eyüp Efe; Sevsay Sevgi̇ (Zootaxa, 2022)
Laboratory rearing of two mite species, Erythraeus (Zaracarus) budapestensis Fain & Ripka, 1998 collected in Turkey and E. (Z.) rupestris (Linnaeus, 1758) sampled in Germany, allowed establishing the correspondence of their larval and postlarval instars. Erythraeus (Z.) iranicus Saboori & Akrami, 2001 syn. nov. is considered a new subjective junior synonym of E. (Z.) budapestensis. Erythraeus (Z.) eleonorae Haitlinger, 1987 syn. nov. and E. (Z.) didonae Haitlinger, 2000 syn. nov. are synonymized with E. (Z.) rupestris. Data on the life history, parasitic associations and habitats are provided, and the status of currently recognized subgenera of Erythraeus is discussed.